Sustainable development and good governance towards digitalization: A quantile analysis - Cheng, Alex Heng Siang (2023)
Sustainable development, good governance, and digitalization are the important concerns for a country in the aspect of economy, social, and environmental. This thesis aims to examine the relationship between sustainable development, good governance, and digitalization, the direct effect of achieving sustainable development and upholding good governance towards digitalization, and the indirect effect from good governance also has been explored. The research apply quantile regression analysis, focuses on 50 countries that are included in the study of IMD World Digital Competitiveness, with the year data from year 2013 to 2020. The results show that achieving sustainable development will reduce a country digitalization level at higher quantile, there is no significant relationship between sustainable development and digitalization at lower and middle quantile. Good governance shows a highly significant positive relationship with digitalization at all quantile, this implies that good governance is an important factor that determine a country’s digitalization level. Specifically, good governance also shows a significant moderating effect on reducing the contradiction between achieving sustainable development and digitalization. Our study provide empirical findings for policy makers on promoting policy coherence and coordination between different sectors and stakeholders, to ensure that sustainable development policies and digitalization strategies are aligned and mutually reinforcing.